2015
DOI: 10.3892/etm.2015.2963
|View full text |Cite
|
Sign up to set email alerts
|

Total flavonoids of Hedyotis diffusa Willd inhibit inflammatory responses in LPS-activated macrophages via suppression of the NF-κB and MAPK signaling pathways

Abstract: Abstract. Nuclear factor κB (NF-κB) and mitogen-activated protein kinase (MAPK) signaling pathways play a central role in inflammatory responses. Total flavonoids of Hedyotis diffusa Willd (TFHDW) are active compounds derived from Hedyotis diffusa Willd, which has been long used in Chinese traditional medicine for the treatment of various inflammatory diseases, including ulcerative colitis and bronchitis; however, the precise mechanisms underlying the effects of TFHDW are largely unknown. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Treating macrophages with OBE before the stimulation with LPS partly counteracted such responses by about 30%. These results are similar to findings from recent studies demonstrating anti-inflammatory properties of polyphenols and other plant bioactives in cell cultures [52; 53] and farm animals [54]. Furthermore, our in vivo and in vitro results indicate that inhibition of IL1B production is a key component of the OBE anti-inflammatory action.…”
Section: Discussionsupporting
confidence: 92%
“…Treating macrophages with OBE before the stimulation with LPS partly counteracted such responses by about 30%. These results are similar to findings from recent studies demonstrating anti-inflammatory properties of polyphenols and other plant bioactives in cell cultures [52; 53] and farm animals [54]. Furthermore, our in vivo and in vitro results indicate that inhibition of IL1B production is a key component of the OBE anti-inflammatory action.…”
Section: Discussionsupporting
confidence: 92%
“…To date, twenty-three phenolic acids (87-109) have been identified from the herb of H. Diffusa, including four benzoic acid derivatives (87)(88)(89)(90), coumaric acid (91) …”
Section: Phenolic Acids and Their Derivativesmentioning
confidence: 99%
“…Moreover, two main chemotypes, including eight flavonoids and four iridoid glycosides were found in renal tissues after H. diffusa treatment, indicating that the anti-inflammatory effect may be due to these constituents [87]. In vitro, Chen et al found that the flavonoids extract treatment (50´100 µg/mL) on LPS-stimulated RAW 264.7 cells reduced expression of iNOS, TNF-α, IL-6 and IL-1β, as well as suppressing phosphorylation of IκB p38, JNK and ERK1/2 in a concentration-dependent manner, indicating that the anti-inflammatory activity of total flavonoids had a close relationship with the NF-κB-and MAPK-signaling pathways [88].…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…Belonging to the Rubiaceae family of plants, HDW is widely distributed in Northeast Asia. It is used in TCM to clear away heat and toxic material (7,8), to promote blood circulation and has long been used clinically to treat various types of cancer, including breast (10), colorectal (11) and liver (12) cancer. Our previous studies demonstrated that HDW inhibited the growth of CRC, possibly by inducing cancer cell apoptosis and inhibiting cell proliferation and tumor angiogenesis (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Hedyotis diffusa Willd (HDW) is a well-known herbal medicine, which exhibits a variety of bioactivities, including anti-inflammatory, antioxidative, immune-modulating and anticancer properties (7)(8)(9). Belonging to the Rubiaceae family of plants, HDW is widely distributed in Northeast Asia.…”
Section: Introductionmentioning
confidence: 99%